2007
DOI: 10.1057/palgrave.jmm.5050136
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes knowledge and physician compliance: Evidence of links in a large South African sample

Abstract: Pretoria, South Africa, where she is also an adjunct professor of surgery at the university. She specialises in the insertion of arterial stents, and runs a diabetic foot clinic. She has taught and researched in Australia, the UK, Canada, the USA and Morocco, and has presented many papers at academic conferences, and published in medical journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another study reported women to be more active in self-care and information-seeking than males [ 16 ]. This apparent knowledge deficit should be a cause for concern to the health-care providers since patients with low diabetes knowledge levels have been reported to be least likely to comply with diabetes management and instructions from health care professionals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported women to be more active in self-care and information-seeking than males [ 16 ]. This apparent knowledge deficit should be a cause for concern to the health-care providers since patients with low diabetes knowledge levels have been reported to be least likely to comply with diabetes management and instructions from health care professionals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes outcome of patients depends primarily on the level of knowledge of the disease, which includes healthy activities and care-seeking that is determined by individual and cultural beliefs about health, illness, and healthcare [18]. It is stated that patients having a low level of knowledge regarding diabetes are least expected to follow given instructions from health-care providers regarding diabetes management [19]. American Association of Clinical Endocrinologists has described the significance of lifestyle changes, self-care and knowledge of people living with diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is already a high level of poor glycaemic control in the EC province [6], probably improving diabetes knowledge could be a positive step towards improving glycaemic control in the province. Likewise, the low level of knowledge is concerning as patients with a poor level of knowledge are least likely to comply with health instructions and regimens which impacts clinical outcomes [31].…”
Section: Plos Onementioning
confidence: 99%